The Antimalarial Chloroquine Reduces the Burden of Persistent Atrial Fibrillation - Tobón, Catalina; Palacio, Laura C.; Chidipi, Bojjibabu; Slough, Diana P.; Tran, Thanh; Tran, Nhi; Reiser, Michelle; Lin, Yu-Shan; Herweg, Bengt; Sayad, Dany; Saiz, Javier; Noujaim, Sami (Frontiers in Pharmacology, 2019)
In clinical practice, reducing the burden of persistent atrial fibrillation by pharmacological means is challenging. We explored if blocking the background and the acetylcholine activated inward rectifier potassium currents (IK1 and IKACh) could be antiarrhythmic in persistent atrial fibrillation. We thus tested the hypothesis that blocking IK1 and IKACh with chloroquine decreases the burden of persistent atrial fibrillation. We used patch clamp to determine the IC50 of IK1 and IKACh block by chloroquine and molecular modeling to simulate the interaction between chloroquine and Kir2.1 and Kir3.1, the molecular correlates of IK1 and IKACh. We then tested, as a proof of concept, if oral chloroquine administration to a patient with persistent atrial fibrillation can decrease the arrhythmia burden. We also simulated the effects of chloroquine in a 3D model of human atria with persistent atrial fibrillation. In patch clamp the IC50 of IK1 block by chloroquine was similar to that of IKACh. A 14 day regimen of oral chloroquine significantly decreased the burden of persistent atrial fibrillation in a patient. Mathematical simulations of persistent atrial fibrillation in a 3D model of human atria suggested that block of IK1 and IKACh prolonged the action potential duration, leading to failure of reentrant excitation, and the subsequent termination of the arrhythmia. The combined block of IK1 and IKACh can be a targeted therapeutic strategy for persistent atrial fibrillation.